KELUARGA INSTITUSI AWAL DALAM MEMBENTUK MASYARAKAT BERPERADABAN - Abdul Wahid; M. Halilurrahman (CENDEKIA: Jurnal Studi Keislaman, 2019)
family is a smaller unit in society but it have big role in cultured state and nation. Success in family institution can be including success in economy, education and occupation or all of them. But, those are not certify to be a hormonious, happy and peaceful family. Being a happy and harmony family is a aim for every single of family. Due to the fact that, to establish a harmony family must be based by islamic theory. Success in organizing a harmony family have a strong related to peaceful society since the society come into being family. In addition, to being a strong and cultured family, parents have to have a skill and ability to creat a conducive sorroundings. Other than that, each part of family have a role active, responsible, good communication and build a love and pity either parents or children, the most important is equal in doing a work based on family need.